Implementation of Firebase Realtime Database to Track BRT Trans Semarang - Wiratno, Andreas Ragil; Hastuti, Khafiizh (Scientific Journal of Informatics, 2017)
Many application developed to help people get information about BRT (Bus Rapid Transit) Trans Semarang. However, the existing application felt less effective and unable to provide what user need. So we proposed a prototype of android based application which able to provide information about BRT Trans Semarang in an effective ways. The developed system contains two application, that is driver side application and user side application. The reason for using Firebase Realtime Databse is because of every data changes in database it will synchronize to the user automatically without waiting user to refresh or reload the application. Our proposed method is well designed and implemented and succeed to provides what user need which proved by a user acceptance test